Learning approaches as constraints to education capabilities development among students of social sciences at Makerere University, Uganda - Bigabwenkya, S. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
Graduates of social sciences at Makerere University in Uganda have apparently low levels of higher education capabilities as evidenced in low labour productivity, due to, among other things, deficiencies in knowledge, skills and attitudes. Using data from interviews of five alumni, four lecturers of social sciences, and document reviews the author established that learning approaches used by most students quite often constrain their level of higher education capabilities development. While these students use the common learning methods such as group discussions, doing coursework, attending lectures and person reading; their levels of engagement with the subject matter are surface in nature as opposed to deep learning engagements. Actually, most students do rote-learning when the examinations are approaching and spend the rest of their time engaged in other non-academic activities. Quite often, the students take a minimalist approach to learning and are just interested in getting a degree regardless of the education capabilities developed. In this paper, I argue that the surface approach to learning used by students of social sciences at Makerere University limits their development of higher education capabilities. I therefore suggest that in order to develop the relevant education capabilities among students at Makerere University, and probably other universities in Africa, the authorities need to motivate students to learn; teach students how to learn; and develop analytical skills in students for the future development of Africa.
Journal article published in the 3rd Annual International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Deep approach to learning; Higher education capabilities; Learning; Surface approach to learning; Education, Higher -- Uganda; Learning -- Evaluation; Social sciences -- Study and teaching